A critical analysis of building sustainability assessment methods for healthcare buildings - Castro, Maria de Fátima Morais de Aguiar e (2015)
The healthcare building project contains different aspects from the most common projects. Designing a healthcare environment is based on a number of criteria related to the satisfaction and well-being of the professional working teams, patients and administrators. Mostly due to various design requirements, these buildings are rarely designed and operated in a sustainable way. Therefore, the sustainable development is a concept whose importance has grown significantly in the last decade in this sector. The worldwide economic crisis reinforces the growing environmental concerns as well as raising awareness among people to a necessary and inevitable shift in the values of their society. To support sustainable building design, several building sustainability assessment (BSA) methods are being developed worldwide. Since healthcare buildings are rather complex systems than other buildings, so specific methods were developed for them. These methods are aimed to support decision-making towards the introduction of the best sustainability practices during the design and operation phases of a healthcare environment. However, the comparison between the results of different methods is difficult, if not impossible, since they address different environmental, societal and economic criteria, and they emphasize different phases of the life cycle. Therefore, the aim of this study was to clarify the differences between the main BSA methods for healthcare buildings by analysing and categorizing them. Furthermore, the benefits of these methods in promoting a more sustainable environment will be analysed, and the current situation of them within the context of standardization of the concept sustainable construction will be discussed.